DO AUTOMATION AND DATA ALWAYS IMPROVE EFFICIENCY? THE MEDIATING ROLE OF TECHNOLOGY READINESS IN SERVICE CONTEXTS - Sri Astuti Mualimin; Mega Utami; Ramlawati; Serlin Serang (Accounting Profession Journal (APAJI), 2026)
This study examines whether service automation and customer data utilisation consistently improve service efficiency, with a particular focus on the mediating role of Technology Readiness Index. Using a quantitative approach, data were collected from 160 employees working in digitally enabled service organisations and analysed using Partial Least Squares Structural Equation Modelling. The findings reveal that service automation does not have a direct effect on service efficiency, while customer data utilisation significantly enhances efficiency. Technology readiness emerges as a critical determinant, exerting the strongest direct influence on service efficiency. Furthermore, technology readiness fully mediates the relationship between service automation and service efficiency, indicating that automation contributes to performance only when it enhances individuals’ readiness to engage with technology. In contrast, the mediating effect of technology readiness in the relationship between customer data utilisation and service efficiency is not supported. These results suggest that different digital technologies operate through distinct mechanisms, highlighting the importance of human readiness in realising the benefits of automation. This study contributes to the literature by challenging deterministic views of digital transformation and emphasising the conditional role of technology in improving organisational performance.